123k views
5 votes
Solve for y: x(y-3)=2y+1

2 Answers

3 votes

Answer:


y = (3x + 1)/(x - 2)

Explanation:

Add -2y to both sides:

xy−3x+−2y=2y+1+−2y

Simplify:

xy−3x−2y=1

Add 3x to both sides:

xy−3x−2y+3x=1+3x

Simplify:

xy−2y=3x+1

Factor out variable y:

y(x−2)=3x+1

Divide both sides by x-2:


(y(x - 2))/(x - 2) = (3x + 1)/(x - 2)

Simplify:


y = (3x + 1)/(x - 2)

Hope this helps :)

User Daniel Mora
by
4.3k points
0 votes

Answer: y=(3x+1)/(x-2)

Step-by-step explanation: Step by step with principles included in the image.

Solve for y: x(y-3)=2y+1-example-1
User Ivnext
by
5.0k points